Respuesta :
For this case we have the following system of equations:
[tex]5x + 3y = -18 2x- 4y = -28[/tex]
We can rewrite the system of equations to clear the variable y.
We have then:
[tex]10x + 6y = -36 10x- 20y = -140[/tex]
Adding both equations we have:
[tex]6y - 20y = -176 -14y = -176[/tex]
Answer:
An expression that gives the y-coordinate of the solution of the system is:
[tex]-14y = -176[/tex]
[tex]5x + 3y = -18 2x- 4y = -28[/tex]
We can rewrite the system of equations to clear the variable y.
We have then:
[tex]10x + 6y = -36 10x- 20y = -140[/tex]
Adding both equations we have:
[tex]6y - 20y = -176 -14y = -176[/tex]
Answer:
An expression that gives the y-coordinate of the solution of the system is:
[tex]-14y = -176[/tex]
Answer:
3 ( y+6 ) = 10( 7-y ) is the answer.
Step-by-step explanation:
The given equations are 5x + 3y = -18 and 2x - 4y = -28
We have to find the expression that gives the coordinate of the solution of the system.
5x + 3y = -18
5x = 18 - 3y
x = [tex]\frac{-3(y+6)}{5}[/tex] -----------(1)
2x - 4y = -28
x = -2y = - 14
x = -14 + 2y
x = -2 (7 - y) ----------(2)
Now we will equate both the equations (1) and (2)
-[tex]\frac{3}{5}[/tex] ( y + 6 ) = -2 ( 7-y )
3 ( y+6 ) = 10( 7-y )
Therefore, 3 ( y+6 ) = 10( 7-y ) is the answer.